Psychology teaching methods: problems and perspectives - Qafarova Simuzər Mürvət qızı (World Scientific Reports, 2024)
The modernization of the psychology teaching process requires the implementation of new methods and approaches, such as active teaching methods and modern technologies. This article discusses the importance of psychological preparation for future specialists, emphasizing the role of active learning and the integration of technology into the educational process. These methods contribute to improving the quality of education, positively impacting both academic and personal development of students